Darbepoetin alfa injection versus epoetin alfa injection for treating anemia of Chinese hemodialysis patients with chronic kidney failure: A randomized, open‐label, parallel‐group, non‐inferiority Phase III trail - Nan Chen; Changying Xing; Jianying Niu; Bicheng Liu; Junzhou Fu; Jiuyang Zhao; Zhaohui Ni; Mei Wang; Wenhu Liu; Jinghong Zhao; Ling Zhong; Xiongfei Wu; et al. (Chronic Diseases and Translational Medicine, 2022)
Abstract Background Erythropoietin is a glycoprotein that mainly regulates erythropoiesis. In patients with chronic renal failure with anemia, darbepoetin alfa can stimulate erythropoiesis, correct anemia, and maintain hemoglobin levels. This study was designed to demonstrate the efficacy and safety of darbepoetin alfa injections as being not inferior to epoetin alfa injections (Recombinant Human Erythropoietin injection, rHuEPO) when maintaining hemoglobin (Hb) levels within the target range (10.0–12.0 g/dL) for the treatment of renal anemia. Methods Ninety‐five patients were enrolled in this study from April 15, 2013 to April 10, 2014 at 25 sites. In this study, patients (n = 95) aged 18–70 years were randomized into a once per week intravenous darbepoetin alfa group (n = 56) and a twice or three times per week intravenous epoetin alfa group (n = 39) for 28 weeks, who had anemia with hemoglobin levels between 6 g/dL and 10 g/dL due to chronic kidney disease (CKD) and were undergoing hemodialysis or hemofiltration with ESA‐naive (erythropoiesis stimulating agent‐naive). The primary efficacy profile was the mean Hb level (the non‐inferiority margin was −1.0 g/dL, week 21–28); the secondary efficacy profiles were the Hb increase rate (week 0–4), the target Hb achievement cumulative rate and time, the change trends of the Hb levels, and the target Hb maintenance ratio. Adverse events (AEs) were observed and compared, and the efficacy and safety were analyzed between the two treatment groups. Additionally, the frequencies of dose adjustments between the darbepoetin alfa and epoetin alfa groups were compared during the treatment period. SAS® software version 9.2 was used to perform all statistical analyses. Descriptive statistics were used for all efficacy, safety, and demographic variable analyses, including for the primary efficacy indicators. Results The mean Hb level was 11.3 g/dL in the darbepoetin alfa group and 10.7 g/dL in the epoetin alfa group, respectively; the difference of the lower limits of the 95% confidence intervals (CI) between the two groups was 0.1 g/dL (>−1.0 g/dL), and non‐inferiority was proven; the Hb levels started to increase in the first four weeks at a similar increase rate; no obvious differences were observed between the groups in the target Hb achievement cumulative rates, and the Hb levels as well as the target Hb level maintenance rate changed over time. The incidence of AEs was 62.5% in the darbepoetin alfa group and 76.9% in the epoetin alfa group. All the adverse events observed in the study were those commonly associated with hemodialysis. Conclusion Darbepoetin alfa intravenously once per week can effectively increase Hb levels and maintain the target Hb levels well, which makes it not inferior to epoetin alfa intravenously twice or three times per week. Darbepoetin alfa shows an efficacy and safety comparable to epoetin alfa for the treatment of renal anemia.